Hyperthermia impairs Sertoli cell functions. Effects on lipid metabolism - Valles, Ana Sofia (2013)
Spermatogenesis is known to be vulnerable to temperature. Previous work from our group showed that in vivo testicular hyperthermia selectively damages germ cells at specific developmental stages and rapidly induces a seminiferous epithelium involution. This concurred with a considerable buildup of lipid droplets in Sertoli cells (SC). The aim of this study was to examine the effects of heat exposure on isolated SC in culture. Warming to 43ºC disrupted SC microtubule network and actin microfilaments. This SC cytoskeleton perturbation was accompanied by increased ROS production, mitochondrial depolarization, and accumulation of triacylglicerols (TAG). The heat exposure-dependent TAG accumulation could be explained by an impairment of mitochondrial fatty acid oxidation and a re-direction of fatty acids into TAG synthesis and lipid droplet formation. The impaired mitochondrial physiology also reduced the de novo synthesis of cardiolipin, as observed after incubating SC cultures with [3H]arachidonic acid. The hyperthermia-induced cytoskeletal and mitochondrial alterations could in part respond for the lipid metabolic disorder that SC undergo. Since these cells provide support to germ cells, these changes might be one of the underlying causes of the temporal impairment of spermatogenesis observed in vivo during testicular hyperthermia.